Exploring the Medicinal Properties and Health Benefits of Essential Oils in Treatment - Akram, Muhammad; Abbas, Sabahat; Umaru, Isaac John (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Essential oils are hydrophobic liquids extracted from plants by using different solvents and steam distillation procedures. They are rich in secondary metabolites, mainly terpenoids and phenylpropanoids. These metabolites provide a special aroma and strong pharmacological actions against different diseases and skin irritants. They are widely used as antifungal, antibacterial, anti-inflammatory, antidiabetic, antiviral, anti-carcinogenic, antioxidant, and anti-saying agents. The main aim of this review is to discuss the main sources or concentrations of factors affecting EOs and extensively analyze the major phytochemicals that are used for treating different diseases. In conclusion, essential oils were found to be promising agents for their anti-saying, antioxidant, and antimicrobial activities. Further studies should focus on a more detailed mechanism of their action and other possible benefits, especially to the cosmetic and pharmaceutical industries.